Lysosomal-Associated Protein Transmembrane 5 Functions as a Novel Negative Regulator of Pathological Cardiac Hypertrophy - Gao, Lu; Guo, Sen; Long, Rui; Xiao, Lili; Yao, Rui; Zheng, Xiaolin; Zhang, Yanzhou; Wang, Xiaofang (Frontiers in Cardiovascular Medicine, 2021)
Lysosomal-associated protein transmembrane 5 (LAPTM5) is mainly expressed in immune cells and has been reported to regulate inflammation, apoptosis and autophagy. Although LAPTM5 is expressed in the heart, whether LAPTM5 plays a role in regulating cardiac function remains unknown. Here, we show that the expression of LAPTM5 is dramatically decreased in murine hypertrophic hearts and isolated hypertrophic cardiomyocytes. In this study, we investigated the role of LAPTM5 in pathological cardiac hypertrophy and its possible mechanism. Our results show that LAPTM5 gene deletion significantly exacerbates cardiac remodeling, which can be demonstrated by reduced myocardial hypertrophy, fibrosis, ventricular dilation and preserved ejection function, whereas the opposite phenotype was observed in LAPTM5 overexpression mice. In line with the in vivo results, knockdown of LAPTM5 exaggerated angiotensin II-induced cardiomyocyte hypertrophy in neonatal rat ventricular myocytes, whereas overexpression of LAPTM5 protected against angiotensin II-induced cardiomyocyte hypertrophy in vitro. Mechanistically, LAPTM5 directly bound to Rac1 and further inhibited MEK-ERK1/2 signaling, which ultimately regulated the development of cardiac hypertrophy. In addition, the antihypertrophic effect of LAPTM5 was largely blocked by constitutively active mutant Rac1 (G12V). In conclusion, our results suggest that LAPTM5 is involved in pathological cardiac hypertrophy and that targeting LAPTM5 has great therapeutic potential in the treatment of pathological cardiac hypertrophy.